Benefit and harm of pregabalin in acute pain treatment: a systematic review with meta-analyses and trial sequential analyses. (6th September 2017) - Fabritius, M. L.; Strøm, C.; Koyuncu, S.; Jæger, P.; Petersen, P. L.; Geisler, A.; Wetterslev, J.; Dahl, J. B.; Mathiesen, O.
Abstract: Pregabalin has demonstrated anti-hyperalgesic properties and was introduced into acute pain treatment in 2001. Our aim was to evaluate the beneficial and harmful effects of pregabalin in postoperative pain management. We included randomized clinical trials investigating perioperative pregabalin treatment in adult surgical patients. The review followed Cochrane methodology, including Grading of Recommendations Assessment, Development, and Evaluation (GRADE), and used trial sequential analyses (TSAs). The primary outcomes were 24 h morphine i.v. consumption and the incidence of serious adverse events (SAEs) defined by International Conference of Harmonisation Good Clinical Practice guidelines. Conclusions were based primarily on trials with low risk of bias. Ninety-seven randomized clinical trials with 7201 patients were included. The 24 h morphine i.v. consumption was reported in 11 trials with overall low risk of bias, finding a reduction of 5.8 mg (3.2, 8.5; TSA adjusted confidence interval: 3.2, 8.5). Incidence of SAEs was reported in 21 trials, with 55 SAEs reported in 12 of these trials, and 22 SAEs reported in 10 trials with overall low risk of bias. In trials with overall low risk of bias, Peto's odds ratio was 2.9 (1.2, 6.8; TSA adjusted confidence interval: 0.1, 97.1). Based on trials with low risk of bias, pregabalin may have a minimal opioid-sparing effect, but the risk of SAEs seems increased. However, the GRADE-rated evaluations showed only moderate to very low quality of evidence. Consequently, a routine use of pregabalin for postoperative pain treatment cannot be recommended.